Diagnostic performance of plasma Aβ42/40 ratio, p-tau181, GFAP, and NfL along the continuum of Alzheimer's disease and non-AD dementias: An international multi-center study - Doecke, James D; Bellomo, Giovanni; Vermunt, Lisa; Alcolea, Daniel; Halbgebauer, Steffen; In 't Veld, Sjors; Mattsson-Carlgren, Niklas; Veverova, Katerina; Fowler, Christopher J; Boonkamp, Lynn; Houtkamp, Isabel M; Koel-Simmerlink, Marleen; et al. (Alzheimer's & dementia, 2025)
INTRODUCTION: Plasma phosphorylated tau (p-tau)181, glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL), and amyloid beta ratio (Aβ42/40) may have diagnostic and prognostic value in Alzheimer's disease (AD). Here we assess which markers can best identify AD from controls and other non-AD dementias in a large international multi-center study. METHODS: Plasma samples (n = 1298) were collected from six international centers. Aβ40, Aβ42, GFAP, NfL, and p-tau181 were measured using single molecule array. In each group, AD diagnosis/co-pathology was defined according to cerebrospinal fluid biomarkers or amyloid positron emission tomography. Validations were performed in three separate cohorts via single and dual cut-off models. RESULTS: p-tau181 showed the best area under the curve value to separate AD from frontotemporal dementia, controls, and Aβ- dementia with Lewy bodies. However, this discriminative power could not be reproduced by applying pre-defined cut-offs. DISCUSSION: p-tau181 was the best single plasma marker for detecting AD at any stage. Specific cut-offs are needed to maximize diagnostic performances. HIGHLIGHTS: Phosphorylated tau (p-tau)181 provided a clear differentiation between controls and Alzheimer's disease (AD) participants, with evidence of increased levels in the preclinical stage of AD. Plasma biomarkers demonstrated that when amyloid co-pathology is removed from dementia with Lewy bodies (DLB), only glial fibrillary acidic protein and neurofilament light chain remain to predict DLB. Given the low prevalence of amyloid co-pathology in frontotemporal dementia (FTD), p-tau181 and its ratio with amyloid beta 42 are strong biomarkers to differentiate FTD from AD.
Keywords: proteiny tau; Male; Dementia; biologické markery; Biomarkers; demence; fosforylace; Phosphorylation; Alzheimerova nemoc; Alzheimer Disease; Aged; mužské pohlaví; senioři; amyloidní beta-protein; tau Proteins; Neurofilament Proteins; peptidové fragmenty; lidé; ženské pohlaví; Amyloid beta-Peptides; Humans; gliový fibrilární kyselý protein; Glial Fibrillary Acidic Protein; Peptide Fragments; Female; lidé středního věku; neurofilamentové proteiny; Middle Aged